An Earplug Technique to Reduce the Gag Reflex during Dental Procedures - TEZULAŞ, EMRE; ÖZDOĞMUŞ, NECMETTİN ÖMER (KARGER, 2014)
Background: The gag reflex is a frequent problem occurring during dental treatment procedures, especially while making impressions of the maxillary teeth. The present study aims to evaluate the efficacy of a simple earplug as an external auditory canal stimulator to supress the profound gag reflex and as a second step, to map areas of the oropharynx suppressed by this technique. Methods: In the first step of the study, 90 patients who had a gag reflex during the impression procedure were allocated to a study group, a sham group, and a control group for evaluating the efficacy of the earplug technique. Second, 20 new patients with a gag reflex were included in order to map the oropharnygeal areas suppressed by this technique. Results: The severity of the gag reflex was reduced in the earplug group (but not in the sham or the control group). The affected area included the hard palate, uvula, and the tongue but not the posterior wall of oropharynx. Conclusion: An earplug technique can be a useful, practical, and effective tool to overcome the gag reflex during oral procedures, such as impression procedures of maxillary teeth.
Keywords: Gag reflex; Earplug; Trigeminal; Glossopharyngeus; Oral; AURICULOTEMPORAL NERVE; VAGUS NERVE; EAR; ACUPUNCTURE; STIMULATION; ANATOMY; OTALGIA; COUGH; POINT